Superbird - Tomlinson, Brian (Cambridge English readers. Level 2, 1999)
A spaceship crashes on a strange planet and everyone on it dies, except for one person . She helps the people of the planet to build their own spaceship, and returns home in it. But when she is back home with her own people, the real trouble begins.